2020
DOI: 10.2807/1560-7917.es.2020.25.36.2001542
|View full text |Cite
|
Sign up to set email alerts
|

Reduced maximal aerobic capacity after COVID-19 in young adult recruits, Switzerland, May 2020

Abstract: In March 2020, we observed an outbreak of COVID-19 among a relatively homogenous group of 199 young (median age 21 years; 87% men) Swiss recruits. By comparing physical endurance before and in median 45 days after the outbreak, we found a significant decrease in predicted maximal aerobic capacity in COVID-19 convalescent but not in asymptomatically infected and SARS-CoV-2 naive recruits. This finding might be indicative of lung injury after apparently mild COVID-19 in young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
74
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 10 publications
12
74
0
3
Order By: Relevance
“…These problems are worth further exploration. The results of the present study are consistent with those published by other researchers, who reported similar impaired physical fitness in athletes during the same period [ 54 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 94%
“…These problems are worth further exploration. The results of the present study are consistent with those published by other researchers, who reported similar impaired physical fitness in athletes during the same period [ 54 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 94%
“…There were two prospective and eight retrospective cohort studies and one case report containing information regarding the respiratory system [ 14 , 15 , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , 24 ,]].…”
Section: Resultsmentioning
confidence: 99%
“…Eight out of 11 studies used computed tomography [ [16] , [17] , [18] , [19] , [21] , [22] , [23] , [24] ]. Six out of 11 performed a lung function test [ [14] , [15] , [16] , 20 , 23 , 24 ]. Follow-up intervals ranged from nine days to three months post-discharge from hospital.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IRBs are charged with making that assessment, but in the case of human challenge studies, knowledge about infection with SARS-CoV-2 and potential resulting COVID-19 illness continues to evolve; many unknowns remain. Despite the earlier belief that young, healthy adults (the proposed subjects) experience a mild form of COVID-19 and recover quickly, recent data have revealed that this population can experience significant adverse effects when they become infected (22)(23)(24). An additional shortcoming of HCS is that some risks of the vaccine itself may emerge only when a larger number of individuals have been vaccinated.…”
Section: Acceptable Risk-benefitmentioning
confidence: 99%